HUBUNGAN TINGKAT PENGETAHUAN DAN PERILAKU PERSONAL HYGIENE TERHADAP KEJADIAN PEDIKULOSIS PADA ANAK SD DI NUSA PENIDA - Bisma Krisnanda, I Kadek; Sri Laksemi, Dewa Ayu Agus; Asri Damayanti, Putu Ayu; Eka Diarthini, Ni Luh Putu (E-Jurnal Medika Udayana; Vol 13 No 8 (2024): E-Jurnal Medika Udayana, 2024)
ABSTRACT   Pediculosis capitis is an infection that occurs on the human scalp due to an infestation of Pediculus humanus capitis. Pediculosis is characterized by itching on the scalp, in school-age children the infestation of Pediculus humanus capitis has a negative impact on children's learning activities and has the potential to interfere with learning achievement. This study aims to determine whether personal hygiene and knowledge have a relationship with the incidence of pediculosis in elementary school children in Nusa Penida. This study uses an analytic observational study with a Cross Sectional study with univariate analysis techniques and bivariate analysis using the Chi-square test, this study used a sample of 100 samples taken from SD Negeri 2 Ped and SD Negeri 4 Ped, data collection was carried out by using a questionnaire regarding personal hygiene behavior and knowledge of pediculosis and the incidence of pediculosis in research respondents. In this study it was found that out of 100 respondents, 44% had poor personal hygiene, 41% had poor knowledge and 65% experienced pediculosis which is a high number because it exceeds 50% , from this study it was found that personal hygiene had a significant relationship with the incidence of pediculosis (p-value 0.002 and RP = 1.580), and knowledge about pediculosis has a relationship with the incidence of pediculosis (p-value 0.002 and RP = 1.578). So it can be seen that personal hygiene and knowledge about pediculosis is one of the risk factors for the incidence of pediculosis in elementary school children in Nusa Penida. Keywords : Personal hygiene, Knowledge, Pediculosis